Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/bmj.k1951
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant utilisation and incidence of weight gain during 10 years’ follow-up: population based cohort study

Abstract: ObjectiveTo evaluate the long term association between antidepressant prescribing and body weight.DesignPopulation based cohort study.SettingGeneral practices contributing to the UK Clinical Practice Research Datalink, 2004-14.Participants136 762 men and 157 957 women with three or more records for body mass index (BMI).Main outcome measuresThe main outcomes were antidepressant prescribing, incidence of ≥5% increase in body weight, and transition to overweight or obesity. Adjusted rate ratios were estimated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
108
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 25 publications
4
108
1
4
Order By: Relevance
“…This research priority includes specific attention to gestational diabetes mellitus, hypertension, fetal growth monitoring and other complications, all with direct implications on pregnancy and offspring outcomes and that interact with maternal lifestyle, BMI and gestational weight gain [7]. Risk profiling and medications (including use of antipsychotic and antidepressant medications that are linked with weight gain [33]) are also included here. This priority focuses on ensuring pregnancy-specific factors relating to health are adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This research priority includes specific attention to gestational diabetes mellitus, hypertension, fetal growth monitoring and other complications, all with direct implications on pregnancy and offspring outcomes and that interact with maternal lifestyle, BMI and gestational weight gain [7]. Risk profiling and medications (including use of antipsychotic and antidepressant medications that are linked with weight gain [33]) are also included here. This priority focuses on ensuring pregnancy-specific factors relating to health are adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot state with certainty whether AD were initially prescribed to obese patients or if prescribing AD contributed to a greater proportion of obese patients with AD prescriptions. The latter possibility, however, is of equal concern, since utilization of AD may contribute to increasing the risk of a long-term weight gain at the population level, moving normal weight and overweight patients to the obesity group (22). It has been reported that at least 1.5% of the obesity rate increase among young adults in the USA during the last two decades can be explained by the increase in the prevalence of depression and AD use (54).…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative, therefore, to evaluate the prevalence and patterns of prescribing pharmacological treatment to patients with depression and comorbid obesity and to examine the association between obesity and AD prescribing. To our knowledge, very few studies (21,22) evaluated how health providers prescribe AD to obese and overweight patients with depression; they showed that utilization of AD may be contributing to population-level increases in excess weight [(22), UK] and that obese patients are less likely to receive recommended standards of care [(21), USA]. To our knowledge, no study evaluated the prevalence and patterns of AD prescribing to patients with obesity in Canada or the association of certain prescribing patterns with the class of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacotherapy is an effective treatment of major depression and antidepressants are among the most commonly prescribed drugs in most Western countries . Consequently, the potential side‐effects of antidepressants have been the subject of considerable attention . Especially after the introduction of selective serotonin reuptake inhibitors (SSRI) on the market, reports of suicidality and aggressive behaviour emerged and eventually led to warnings issued by regulatory agencies in several countries .…”
Section: Introductionmentioning
confidence: 99%